G protein‐coupled receptor 40 expression in human melanoma – correlation with tumour thickness, AJCC stage and survival. (31st October 2019) - Kleemann, J.; Hrgovic, I.; Kleimann, P.; Ter‐Nedden, J.; Glaser, M.; Steinhorst, K.; Härle, K.; Müller, J.; Kaufmann, R.; Kippenberger, S.; Meissner, M.
Abstract: Background: In melanoma, preclinical data suggest a possible role of polyunsaturated fatty acids inhibiting cell growth. A new target molecule for free fatty acids, the G protein‐coupled receptor GPR40, was identified in melanoma cells. Objectives: The aim of this study was to investigate GPR40 expression in human melanocytic tissues and to evaluate its potential as a prognostic marker. Methods and Results: A total of 114 tissue sections of naevi, primary melanoma and melanoma metastasis were immunohistochemically stained with anti‐GPR40. The staining was evaluated, using the immunoreactivity scoring system. Compared to naevi, primary melanoma and melanoma metastasis showed significantly higher levels of GPR40 ( P < 0.05). In primary melanoma, GPR40 expression positively correlated with tumour thickness ( P = 0.044) and AJCC level ( P = 0.017) and in melanoma metastasis with AJCC level ( P = 0.035). Primary melanoma patients with high levels of GPR40 had a significantly poorer overall survival ( P = 0.004) and shorter disease‐free survival (0.040). Conclusion: The present study identified GPR40 as a novel target molecule in melanoma. First evidence for a potential role of the receptor in tumour progression and metastases was found, and it could be demonstrated that GPR40 expression is negatively correlated with patient's survival.